Some peculiarities of the near-surface air temperature change in the Antarctic Peninsula region - V.E. Tymofeyev (Ukrainian Antarctic Journal, 2014)
Current climate in the Antarctic Peninsula (AP) region can be interpreted as a continued warming, still exceeding climatic norms but without significant rise on the Antarctic Peninsula stations. Assessments of trends in the near-air temperatures are made by applying homogeneity procedure and series of monthly SAT normalizing by amplitudes. The most intensive increase in surface air temperature at the end of XX - beginning XXI century recorded at Vernadsky and Rothera stations at the west coast of the Antarctic Peninsula. Most of inhomogeneities are observed in coldest decade, 1950s; current period is characterized by smoothening in the near-surface temperatures (SAT) ranges especially in comparison to 1950s because of changes in atmospheric circulation. Normalized SAT series is comparable between winter and summer seasons at west coast of AP, including Vernadsky and Rothera stations. Spatial and temporal characteristics of near surface temperatures are described, with significant seasonal and topography-dependant variability. Significant differences exist between stations at the west coast and those lying at Weddell Sea coast, especially in summer. By the Vernadsky data, summer warming is mainly responsible for the recession of glaciation. Modern regional warming is associated with growing influence of El Niño-Southern Oscillation, especially after well-known climatic shift in the 1970s due to increased surface temperature of the equatorial Pacific. On the background the overall warming trend some intradecadal SAT fluctuations are registered being associated with El Niño. On the basis of the recent SAT variability at other stations and multi-years’ change in climate indexes it is concluded that no further warming can be expected in the near future.